(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The paper contains the results of the study of the seasonal growth rhythm for the endemic species Allium decipiens (Аlliaceae) at cultivation in Nothern Black Sea Region for the first time. Observations for generative plants were carried out for six years. The plants pass all stages of growth, regularly flower and bear fruit in introduction conditions. It was determined for the first time that duration of its vegetation does not coincide with the general duration of the plants’ growth. Seasonal growth depends from the sum of effective temperatures, which is above 0˚С for this species, and precipitation amounts. Renewal of growth is observed from the third decade of February. А. decipiens belongs to short-vegetating ephemeroids in condition of the Nothern Black Sea Region. It is completely finish growth during three months. The vegetation and flowering are finished before coming of the drought. Average duration of the vegetation is about 64 days. It coincides with flowering in the medium layer of inflorescence in the second decade of May, where after leaves die off. Arrowing of А. decipiens lasts from the third decade of March until the third decade of April. The flowering of the plants is observed in May, and it lasts for a month. Seasonal growth of the plants continues 113 days and finishes at the first decade of July. The most duration has a period of the plants’ vegetation, the least – interstage periods from the beginning of arrowing until the flowering finishing. Correlation between the duration of the vegetation and duration of the generative bodies development is 0.84. It testifies that duration of the pre-generative period less than of the generative one. The average variation coefficient of growth stages duration for the А. decipiens at introduction in Nothern Black Sea Region for six years was 28.3%. The sum of effective temperatures are 830.25˚С and 90.32 mm of precipitation are accumulated. The seasonal growth cycle includes 1704˚С and 151.62 mm of precipitation for the plant vegetation. There is a very high correlation between the average duration of interstage periods, mean-day temperatures and precipitation (0.9451 and 0.9836 respectively). The species in the conditions of introduction is middle-vegetating spring-flowering ephemeroid with a short duration of flowering.